Fish: a new xenograft source for maxillary sinus lifting - Emrah Soylu; Musab Süleyman Kilavuz; Fatih Duman; Hasan Ekeer; Zeynep Burçin Gönen; Beyza Kahraman; Arzu Hanım Yay; Demet Bolat (Journal of Applied Oral Science)
Abstract Objective: Although autogenous grafting is accepted as the gold standard in intraoral grafting, xenogenous grafts are frequently used in sinus lift surgeries due to their osteoinductive and osteoconductive properties. This study aimed to investigate the efficacy of fish spine-derived xenogenic grafts in sinus augmentation surgery. Material and Methods: In this study, a fish spine-derived xenogenic graft was produced for comparison with autogenous graft and bovine derived xenogenic grafts. Twenty-one New Zealand rabbits were used. Autogenous grafts (AG- Group 1), as well as bovine-derived (bHAP - Group 2) and fish spine-derived (fHAP - Group 3) xenogenic grafts were placed in the right and left sinuses of rabbits. The animals were sacrificed at the 4th and 8th weeks. New bone formation (NBF) was evaluated through histological examination, while bone volume (BV), new bone surface/bone volume (BS-BV), new bone surface/tissue volume (BS-TV), and trabecular separation (Tb-Sp) were assessed via Micro-CT. Statistical significance was considered at p<0.05. Results: Histological examination revealed a significant difference in NBF between AG-bHAP (p<0.001), as well as between fHAP-bHAP (p<0.001) in the fourth-week group. No significant difference was found in the eighth-week group (p=0.130). In the eighth-week group, a statistically significant difference was found between fHAP and bHAP in terms of BV. (p=0.007). Conclusion: Although both graft materials used in this study showed positive effects on bone regeneration, fHAP and AG presented similar effects on bone regeneration and were superior to bHAP.